Proposed corporate strategies for Orient Freight International, Inc.: ISO 9001 certified company - Reyes, Maria Teresa L. (Animo Repository, 2002)
Orient Freight, Inc. is a logistics company offering a package of service called the multi-modal transport system. The company belongs to the freight service industry. Formulating a strategic plan for the company was a big challenge, considering the industry to which the company belongs. To be able to know the industry, one should be able to have knowledge about business logistics and all the activities in physically acquiring, moving and storing raw materials, work in process and finished goods inventory from point of origin to point of use. This paper has given me the opportunity to look at the company more closely, to analyze its operations not from an accountant's perspective but from that of a chief executive officer. The proposed strategic plan of the company is derived in a systematic and logical sequence. Proposed strategies was formulated with the analysis of the external and internal environment, which is what Module II and III are all about. This paper presents a logical sequence in formulating a strategy. Module II discusses the relevant changes that are taking place in the environment, which has a material, effects on the industry which Orient Freight International, Inc. belongs. Porter's model of the five forces driving the industry's competition to analyze the industry' structure. This framework has helped identify opportunities that the company should exploit and threats that the company should protect itself from. Models III discusses the internal environment of the company. Analysis was made on the financial position of the company through relevant ratios. Value chain was also used as framework to determine the company's strengths and weaknesses. Determining the strengths and weaknesses is important because strengths will be used to exploit opportunities identified in module II and weaknesses will be used to protect it from threats. Proposed strategies in Module IV are the results of extensive analysis of Module II and III combined. This is the most important module because it includes the actions that the company should take, to compete in a fragmented industry and to achieve a competitive advantage.